Mudharabah Linked Waqf: Inovasi Model Pembiayaan Berkelanjutan untuk UMKM - Majid, Rifaldi (Ikatan Da'i Indonesia, 2022)
This study aims to formulate an innovative financing model and sustainable business assistance through the mudharabah linked waqf scheme. The method used is descriptive qualitative in the form of reviewing scientific journals, books, official news, reports and related regulations which are analyzed by content analysis. Mudharabah linked waqf is an innovation and integration of financing to Micro, Small, and Medium Enterprises (MSMEs) where the composition of the source of funds comes from commercial funds and cash waqf funds managed by Koperasi Syirkah Berkah Bersama (KSBB) through a collaboration with Indonesian Muslim Entrepreneurs Community (KPMI) chapter Surabaya. Funds will be channeled to low-risk MSME projects recommended by KPMI Surabaya with duration of fewer than six months. The surplus of cash waqf will be distributed to social, education, economy and da’wah activites in the form of sustainable business development and fiqh muamalah assistance by KPMI Surabaya and the rest distributed as an incentive to reduce murabahah margins for startups. Risk mitigation is carried out through collateral requirements, guarantor, incentive-compatible contract applications to determine cash flows and related parties in the project, as well as post-project financial audits. This model has implications for strengthening the roles of KSBB and KPMI Surabaya in encouraging literacy, inclusion, and innovation in deepening sustainable Islamic financial products, in order to strengthen the economy of ummah in the real sector.